The Conjecturing Process: Perspectives in Theory and Implications in Practice - María C. Cañadas; Jordi Deulofeu; Lourdes Figueiras; David Reid; Oleksiy Yevdokimov (University of Windsor, 2007)
In this paper we analyze different types and stages of the conjecturing process. A classification of conjectures is discussed. A variety of problems that could lead to conjectures are considered from the didactical point of view. Results from a number of research studies are used to identify and investigate a number of questions related to the theoretical background of conjecturing as well as practical implications in the learning process.